A comparison of earnings justice throughout Europe: Widespread approval in Germany for income distribution according to need and equity - Jule Adriaans; Philipp Eisnecker; Stefan Liebig (DIW Weekly Report, 2019)
The present study compares the perceptions of fairness of national earned incomes between the populations of Germany and the rest of Europe based on recent data from the European Social Survey (ESS). The vast majority of European respondents consider very low gross earned incomes to be unjustly low. By contrast, very high incomes are less frequently considered too high in Germany than they are in the rest of Europe. Nearly half of Europeans believe their own gross earned income is fair, whereby the higher their own income, the more likely they are to consider it fair. It is striking that this correlation is particularly strong in Germany. Respondents in Europe, and especially in Germany, generally consider it fair that goods and burdens are distributed according to need and equity. In contrast, the distributive principles of equality is more frequently rejected in Germany than in other European countries.
Keywords: D31; D63; J30; 330; Europe; earnings justice; principles of justice; social justice